Diagnosis and imaging of neonatal UTIs - Laura Walawender; David S. Hains; Andrew L. Schwaderer (Elsevier, 2020)
Background: The 2011 American Academy of Pediatrics clinical practice guideline recommends when to obtain renal and bladder ultrasound (RBUS) and voiding cystourethrography (VCUG) following febrile urinary tract infection (UTI) for children age 2-24 months. However, there is not consensus about when to obtain imaging in neonates. The objective of this study is to evaluate UTI diagnostic criteria along with RBUS and VCUG in neonates admitted to the NICU in the first 3 months of life. Methods: A retrospective electronic medical record review was performed of neonates admitted to Nationwide Children's Hospital system NICUs between January 2010 and December 2014 with UTI as a primary or secondary diagnosis. Urine culture results were evaluated versus established UTI criteria and renal US and VCUG results were compared. Results: Of 81 patients with a straight catheterized urine culture obtained, 28 patients met laboratory criteria for diagnosis of UTI and all but 4 had a RBUS. Urine cultures had an equal distribution of Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae, and Coagulase negative staphylococcus. RBUS showed dilation of the collecting system in 37.5% of patients with UTI compared to 41.3% without UTI. VCUG showed vesicourteral reflux (VUR) on 41.7% of those with UTI compared to 34.8% without UTI. For patients with UTI, the sensitivity of RBUS for VUR on VCUG was 60% with CI [0.17, 0.93] and specificity was 43% with CI [0.12, 0.80]. In patients without UTI, sensitivity of RBUS for VUR on VCUG was 63% with CI [0.26, 0.90] and specificity was 71% with CI [0.42, 0.90]. Conclusions: Fewer than half of neonates that were diagnosed clinically with UTI met laboratory criteria for a UTI. Positive urine cultures grew a wide variety of organisms. The sensitivity of renal ultrasound for VUR is only about 60%. Key Words: cystitis, cystourethrogram, ultrasound, urinalysis